26 Del. Laws 28-29 (1911) - (:unkn) unknown (My University, 1911)
§ 2: Prohibited the sale of any pistol, revolver, pistol cartridges, revolver cartridges, stiletto, steel or brass knuckles, or other deadly weapons made especially for the defense of one's person, without having a license labeled "Special License to Sell Deadly Weapons." § 3: Prohibited the sale of firearms, ammunition, and other deadly weapons to minors and incompetent persons.
Keywords: LICENSE - DEALERS; TRANSFER - MINORS